2007
DOI: 10.1007/s00253-006-0746-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of tyrosine from sucrose or glucose achieved by rapid genetic changes to phenylalanine-producing Escherichia coli strains

Abstract: Escherichia coli K12 strains producing L-phenylalanine were converted to L-tyrosine-producing strains using a novel genetic method for gene replacement. We deleted a region of the E. coli K12 chromosome including the pheA gene encoding chorismate mutase/prephenate dehydratase, its leader peptide (pheL), and its promoter using a new polymerase chain reaction-based method that does not leave a chromosomal scar. For high level expression of tyrA, encoding chorismate mutase/prephenate dehydrogenase, its native pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…More significantly, the identification and validation of these chromosomal mutations have led us to the construction of a completely genetically defined strain, rpoA14 R , which possesses a titer of 902 mg∕l L-tyrosine and a yield of 0.18 g L-tyrosine/g glucose in 50-ml shake flask cultures. To put these numbers into perspective, this yield on glucose is more than 150% greater than a classically improved L-phenylalanine auxotroph (DPD4195) currently used for the industrial production of L-tyrosine (cultivated under similar conditions) (27) and, when excluding glucose diverted to biomass, represents 85% of the maximum theoretical yield.…”
Section: Resultsmentioning
confidence: 99%
“…More significantly, the identification and validation of these chromosomal mutations have led us to the construction of a completely genetically defined strain, rpoA14 R , which possesses a titer of 902 mg∕l L-tyrosine and a yield of 0.18 g L-tyrosine/g glucose in 50-ml shake flask cultures. To put these numbers into perspective, this yield on glucose is more than 150% greater than a classically improved L-phenylalanine auxotroph (DPD4195) currently used for the industrial production of L-tyrosine (cultivated under similar conditions) (27) and, when excluding glucose diverted to biomass, represents 85% of the maximum theoretical yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, of the three aromatic amino acids derived from the shikimate (SHIK) pathway, the L-tyrosine yield is the lowest, ranging from 0.10 to 0.15 g per g glucose (Table 1). Though Patnaik et al recently reported L-tyrosine titers of over 50 g/liter using E. coli in a 200-liter bioreactor by improving the fermentation and isolation steps (35), the production strain yielded only 0.09 g of L-tyrosine per gram of glucose (33), which is less than 20% of the theoretical yield (Table 1). Further improvement in the yield is needed to make the process as economically competitive as the processes used to synthesize other amino acids, such as L-lysine, L-glutamate, and L-alanine (17,21).…”
mentioning
confidence: 99%
“…Previous L-tyrosine engineering work has most often focused on the transcriptional deregulation of the tyrR and/or trpR regulons, followed by removing the feedback inhibition on two key enzymes, 3-deoxy-D-arabino-heptulosonate (DAHP) synthase (AroG), which catalyzes the first step committed to the shikimate pathway, and the dual-function chorismate mutase/prephenate dehydrogenase (TyrA), which catalyzes the first two steps in L-tyrosine biosynthesis from chorismate (26,33). Coexpression of the rate-limiting enzymes, shikimate kinase (AroK or AroL) and quinate (QUIN)/shikimate dehydrogenase (YdiB), and deletion of the L-phenylalanine branch of the aromatic amino acid biosynthetic pathway have been shown to increase L-tyrosine production (12,25,33). Furthermore, overexpression of phosphoenolpyruvate synthase (PpsA) and transke-tolase A (TktA), altering glucose transport and the use of other carbon sources, such as xylose and arabinose, have also been shown to increase the pools of precursors to the shikimate pathway (1,9,22,26,34,47,48).…”
mentioning
confidence: 99%
“…An L-Phe-producing strain, which was developed by a classical mutagenesis procedure, was converted into an L-Tyr-producing strain by replacing the native promoter of tyrA with the trc promoter. This strain produced 55 g/liter of L-Tyr, with a Y L-Tyr/Glc of 0.3 g/g and a q L-Tyr of around 57 mg/g (dry weight)/h (33,34).…”
mentioning
confidence: 99%